Fort Worth between the World Wars - Rich, Harold (Book collections on Project MUSE., 2020)
"From its early days as a nineteenth-century army outpost through the boom years of cattle drives, Fort Worth established itself as a major city that, to many, was "where the West began." Harold Rich focuses on the successes and struggles that Fort Worth enjoyed and endured in the 1920s and 1930s as the city's fortunes began to be eclipsed by Dallas, Houston, and San Antonio"--